2014
DOI: 10.1088/0957-4484/26/2/024002
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity and photocorrosion of atomic layer deposited ZnO ultrathin films for the degradation of methylene blue

Abstract: ZnO ultrathin films with varied thicknesses of 7-70 nm were prepared at 200 °C on Si and fused quartz substrates by atomic layer deposition (ALD). The impact of film thickness and annealing temperature on the crystallinity, morphology, optical bandgap, and photocatalytic properties of ZnO in the degradation of methylene blue (MB) dye under UV light irradiation (λ = 365 nm) has been investigated deeply. The as-deposited 28 nm thick ZnO ultrathin film exhibits highest photocatalytic activity, ascribed to the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…The intensity of Zn 2p and O 1s peaks are decreased after photoreaction. The XPS results are in good agreement with the recent work reported by Cao et al [51]. It is also revealed that bare ZnO-nt suffers more by photo-corrosion than ZnO-nt@g-C 3 N 4 (20%).…”
Section: åàsupporting
confidence: 91%
“…The intensity of Zn 2p and O 1s peaks are decreased after photoreaction. The XPS results are in good agreement with the recent work reported by Cao et al [51]. It is also revealed that bare ZnO-nt suffers more by photo-corrosion than ZnO-nt@g-C 3 N 4 (20%).…”
Section: åàsupporting
confidence: 91%
“…Fig. 4(b) shows high-resolution XPS spectra for the ZnO samples, revealing two Zn 2p 3/2 and Zn 2p 1/2 peaks at 1021.88 eV and 1044.81 eV with a better symmetry, corresponding to the spin-orbit split in the Zn 2p spectra [21]. The peak separation was of 23 eV, which is in good agreement with the energy splitting of ZnO.…”
Section: Resultssupporting
confidence: 67%
“…It is worth noting that the photo-corrosion of ZnO during the photocatalytic process is a commonly observed phenomenon45. As a consequence, the photo-stability of the ZnO in the composite during the photocatalytic process was tested, by repeating the photo-degradation measurements seven times.…”
Section: Resultsmentioning
confidence: 99%